The Increasing Sophistication of Mobile Media Sharing in Lower-Middle-Class Bangalore - O'Neill, Jacki; Toyama, Kentaro; Chen, Jay; Tate, Berthel; Siddique, Aysha (ACM - Association for Computing Machinery, 2016)
During the first decade of the 21 st century, the rise of mobile feature phones in India saw the development of both an economy of informal media exchange and a culture of active media sharing for entertainment. Mobile phone owners paid for pirated movies and music on the grey market, and they traded them with one another, even using poorly designed mechanisms such as Bluetooth file exchange. In this paper, we update what is known about the dynamic mobile media sharing culture through qualitative interviews conducted with low- and lower-middle-class participants in and around Bangalore. We find that with the increasing penetration of smartphones and data packs, media sharing has not only continued, but has blossomed into a rich and varied range of activity in which mobile owners display sophisticated knowledge and behaviors. Our participants deftly juggle multiple media devices, mobile handsets, SIM cards, storage devices, mobile applications, and cloud services as a way to navigate issues of cost, file size, data bandwidth, physical proximity, and social engagement styles. We consider our findings in the context of domestication and amplification theories of technology.